Resistance and Virulence Surveillance in Escherichia coli Isolated from Commercial Meat Samples: A One Health Approach - Maísa Fabiana Menck-Costa; Ana Angelita Sampaio Baptista; Matheus Silva Sanches; Beatriz Queiroz dos Santos; Claudinéia Emidio Cicero; Hellen Yukari Kitagawa; Larissa Justino; Leonardo Pinto Medeiros; Marielen de Souza; Sergio Paulo Dejato Rocha; Gerson Nakazato; Renata Katsuko Takayama Kobayashi (Microorganisms, 2023)
Escherichia coli is a key indicator of food hygiene, and its monitoring in meat samples points to the potential presence of antimicrobial-resistant strains capable of causing infections in humans, encompassing resistance profiles categorized as serious threats by the Centers for Disease Control and Prevention (CDC), such as Extended-Spectrum Beta-Lactamase (ESBL)—a problem with consequences for animal, human, and environmental health. The objective of the present work was to isolate and characterize ESBL-producing E. coli strains from poultry, pork, and beef meat samples, with a characterization of their virulence and antimicrobial resistance profiles. A total of 450 meat samples (150 chicken, 150 beef, and 150 pork) were obtained from supermarkets and subsequently cultured in medium supplemented with cefotaxime. The isolated colonies were characterized biochemically, followed by antibiogram testing using the disk diffusion technique. Further classification involved biofilm formation and the presence of antimicrobial resistance genes (blaCTX-M, AmpC-type, mcr-1, and fosA3), and virulence genes (eaeA, st, bfpA, lt, stx1, stx2, aggR, iss, ompT, hlyF, iutA, iroN, fyuA, cvaC, and hylA). Statistical analysis was performed via the likelihood-ratio test. In total, 168 strains were obtained, with 73% originating from chicken, 22% from pork, and 17% from beef samples. Notably, strains exhibited greater resistance to tetracycline (51%), ciprofloxacin (46%), and fosfomycin (38%), apart from β-lactams. The detection of antimicrobial resistance in food-isolated strains is noteworthy, underscoring the significance of antimicrobial resistance as a global concern. More than 90% of the strains were biofilm producers, and strains carrying many ExPEC genes were more likely to be biofilm formers (OR 2.42), which increases the problem since the microorganisms have a greater chance of environment persistence and genetic exchange. Regarding molecular characterization, bovine samples showed a higher prevalence of blaCTX-M-1 (OR 6.52), while chicken strains were more likely to carry the fosA3 gene (OR 2.43, CI 1.17–5.05) and presented between 6 to 8 ExPEC genes (OR 2.5, CI 1.33–5.01) compared to other meat samples. Concerning diarrheagenic E. coli genes, two strains harbored eae. It is important to highlight these strains, as they exhibited both biofilm-forming capacities and multidrug resistance (MDR), potentially enabling colonization in diverse environments and causing infections. In conclusion, this study underscores the presence of β-lactamase-producing E. coli strains, mainly in poultry samples, compared to beef and pork samples. Furthermore, all meat sample strains exhibited many virulence-associated extraintestinal genes, with some strains harboring diarrheagenic E. coli (DEC) genes.